CINTA KASIH SUAMI-ISTRI SEBAGAI FONDASI KEHIDUPAN KELUARGA KRISTIANI: Suatu Uraian Moral Kristiani menurut Paus Fransiskus dalam Seruan Apostolik Amoris Laetitia - Moa, Antonius; Hewen, Yordianus Pajo (UNIKA Santo Thomas, 2022)
The development of time which becoming more modern, exposes married couples to various opportunities and challenges to build Christian family life. The development of the modern world which is marked by very rapid progress in the fields of science and technology not only has a very positive impact but also has a very negative impact on the realization of Christian family life. The magnitude of the negative impact that has occurred has resulted in many Christian families, especially Christian husbands and wives, experiencing difficulties in realizing their essence as a communion of love. Responding to situations like this, the Church is required to continuously proclaim and awaken Christian families, especially married couples, about the love of God as the basis, power, direction and goal of Christian family life. Pope Francis through the Apostolic Exhortation Amoris Laetitia invites married couples as main actors in building a Christian family to always cultivate their love as the foundation of Christian family life. Because the strength of the Christian family lies in the ability of married couples to experience and manifest and teach God's love in Christian family life. That means, God's love which is manifested in the love of husband and wife becomes the determining foundation in building the Christian family as a communion of love.